L’effet de l’accompagnement scolaire sur le développement des compétences sociales des élèves de cycle III - Agathe Fanchini (Recherches en Éducation)
While the role of social skills is today reaffirmed in the new Common set of core skills, the effectiveness of school support schemes in the development of these is disputed. A questionnaire survey was thus developed to measure the evolution of different social skills of 855 pupils from 7 to 12 years. Using the double-difference method after matching on a propensity score, the results obtained concern the nature of the values transmitted by the education system. Social skills playing on the success of pupils and encouraged by educational support, are in fact individual strategies of assertiveness while devaluing the social skills of living together or openness to the world.